Uji Performansi Mesin Ice Tube Kapasitas 20 Kg Per Hari dengan Variasi Debit Aliran Air Spray - Maulana, Ahmad; Sunanto, Sunanto (UM Purwokerto Press, 2023)
Ice tube, also known as crystal ice, is generally transparent ice which is cylindrical in shape and has cavities with small pieces. Ice tube is one of the most popular types of ice because it is more practical. Along with the shifting of people's needs from block ice to tube ice, the need for tube ice is increasing. To expand the big opportunities, we need ice tubes that can be made at home with small scale production. With a simple design and at a low cost. ice machine designed to use a vapor compression system. The main components consist of: compressor, condenser, capillary tube, and evaporator with refrigerant using R22. Considering that the tube ice machine is designed at home with a 12V DC pump as a water vacuum and sprays water into the evaporator with a water flow rate of 1.4 liters per minute. To determine the performance of the system with different water flow rates, performance testing was carried out on a tube ice machine with variations in the flow rate of spray water with several voltages, namely at 9 volts, 12 volts and 15 volts. From the tests that have been carried out, the results show that at a voltage of 9 volts it has the lowest efficiency of about 75%, with an evaporator temperature reaching -5.5°C and a condenser temperature of 46°C, at a voltage of 12 volts it has an efficiency of around 77%, with an evaporator temperature reaching -4.25°C and the condenser temperature is 43°C, while at 15 volts it has the highest efficiency of around 82%, with the evaporator temperature reaching -1.06°C and the condenser temperature 39°C. However, the operational cost rates for using an ice tube machine at a voltage of 9 volts, 12 volts and 15 volts are Rp. 634.56,- ; Rp. 765.85, - and Rp. 1223.07,- per kilogram of tube ice for 45 minutes on operational test.